(untitled) (Research, Society and Development, 2020)
This study aimed to identify and evaluate the epidemiological profile of cases of maternal, congenital syphilis and consequent infant deaths resulting from this infection, in the State of Piauí, reported in the period between 2010 and 2018. A retrospective study was carried out, using secondary data from the Health Information and Analysis Center (DATASUS), through the National System of Notifiable Diseases (SINAN) and the Mortality Information System (SIM) of the Piauí State Department of Health (SESAPI). Several important indicators for the disease were correlated, with an increasing number of cases being observed over the years, with a concomitant increase observed with the incidence rate of gestational and congenital syphilis. The number of deaths was high, prenatal care showed a good percentage over the years, although the evidence shows the low quality of this assistance in the aspects: especially late diagnosis during pregnancy and treatment in most cases performed inappropriately . All of these factors culminate in an increase in acquired syphilis, with the possibility of a relationship with the increase in infant mortality. Therefore, it is clear that even with advances in the prevention of syphilis, this disease still affects many women, causing both sequelae and increased infant mortality.